Development of Digital-Based PJOK Subject Teachbooks - Dodi Andika Ar; Hartati, Hartati; Syafaruddin, Syafaruddin (Universitas PGRI Palembang, 2024)
This research aims to develop a digital-based PJOK textbook for class X students at SMK Negeri 1 Palembang. This research uses research and development research methods with the Borg and Gall model (data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, and mass production). The subjects in this research were class X students at SMK Negeri 1 Palembang. Qualitative and quantitative data analysis techniques. This research was carried out at the development stage, namely large-scale trials. Validation of digital-based PJOK textbooks was carried out by material experts, language experts and media experts. The validation results obtained a material expert assessment of 4.8 while the language expert assessment was 4.16 and the media expert assessment was 4.7 with an average value of 4.55 from the expert validation results indicating that the textbook developed was in the valid or suitable category for use. . The development stage consists of evaluation, small group trials and large group trials. The results of group trials from the initial stage of trials carried out, the total score obtained was 3.47, this score places it in the very positive category and is suitable for use as teaching material in the PJOK learning process in class X vocational schools. Based on the main trial results, the total score obtained was 3.60, this score shows that the textbook is in the very positive category and is suitable for use as teaching material in PJOK subjects in class X vocational schools. Future research can test the effectiveness of digital-based PJOK textbooks so that the influence of digital textbooks can be known when used in PJOK learning.